Gender Segregation in Education and Its Implications for Labour Market Outcomes: Evidence from India - Soham Sahoo; Stephan Klasen (Institute of Labor Economics (IZA), 2018)
This paper investigates gender-based segregation across different fields of study at the post-secondary level of schooling, and how that affects subsequent labour market outcomes of men and women. Using a nationally representative longitudinal data-set from India, we provide evidence that there is substantial intra-household gender disparity in the choice of study stream at the higher-secondary level of education. A household fixed effects regression shows that girls are 20 percentage points less likely than boys to study in technical streams, namely science (STEM) and commerce, vis-à-vis arts or humanities. This gender disparity is not driven by gender specific differences in mathematical ability, as the gap remains large and significant even after controlling for individuals' past test scores. Our further analysis on working-age individuals suggests that technical stream choice at higher-secondary level significantly affects the gender gap in labour market outcomes in adult life, including labour force participation, nature of employment, and earnings. Thus our findings reveal how gender disparity in economic outcomes at a later stage in the life-course is affected by gendered trajectories set earlier in life, especially at the school level.
Keywords: I20; J16; J24; 330; post-secondary education; STEM; gender; labour market; India